Parenting Styles, Gadget Use, and Their Impact on Children's Growth and Development - Restu; Yoonush, Muhammad (Journal of Applied Nursing and Health, 2025)
Background: Every parent desires for their children to grow and develop optimally in accordance with their developmental stages. Child development includes various domains such as language, social, fine motor, and gross motor skills. The purpose of this study was to analyze the influence of parenting patterns and gadget use on the growth and development of preschool children. Methods: This study employed an analytical survey design with a cross-sectional approach. The population consisted of 1,049 parents and preschool children, and a sample of 290 respondents was selected. Parenting style and gadget use were considered independent variables, while children’s growth and development were the dependent variables. Data were analyzed using logistic regression. Results: The findings revealed that a majority of mothers practised a democratic parenting style (92.1%), most children had moderate gadget use (72.8%), and 47.9% of children experienced normal growth. The logistic regression analysis showed a significant relationship between parenting style (p = 0.007) and gadget use (p = 0.050) with child development, indicating that both variables influence developmental outcomes. Parenting and gadget use affect children's development, and parents need to identify these factors to promote healthier child growth and development. Conclusion: The importance of guiding parents to apply appropriate parenting styles and regulate gadget use to support optimal child development. Future research should examine additional factors such as content quality, screen time duration, and parental education level to provide a more comprehensive understanding and more targeted interventions.